Respons Pertumbuhan dan Hasil Tanaman Edamame terhadap Pemberian Pupuk Guano dan Biochar Sekam Padi di Tanah PMK - Devita, Kajol; Supriyanto, Supriyanto; Syahputra, Edy (Fakultas Pertanian Universitas Tanjungpura, 2025)
Edamame (Glycine max (L.) Merrill) is a type of soybean that can be consumed as a vegetable or snack. PMK soil has several limitations, including compact soil structure and low nutrient content. One way to address these issues is by applying guano fertilizer and rice husk biochar. This study aims to determine the growth response and yield of edamame soybeans to the application of guano fertilizer and rice husk biochar in PMK soil, to examine the interaction between guano fertilizer and rice husk biochar in PMK soil, and to identify the optimal dosage of guano fertilizer and rice husk biochar for enhancing the growth and yield of edamame soybeans in PMK soil. The research was conducted on the land of Asrama Mahasiswa Bengkayang, Bansir Darat, Pontianak Southeast and was conducted in the month June-August 2024. The experimental design used was a factorial completely randomized design (RAL) consisting of two factors. The first factor was the application of guano fertilizer with doses of g1 = 8 ton/ha, g2 = 10 ton/ha, and g3 = 12 ton/ha. The second factor was the application of rice husk biochar with doses of b1 = 8 ton/ha, b2 = 10 ton/ha, and b3 = 12 ton/ha.The results showed that guano fertilizer influenced plant height at 3 and 4 weeks after planting (WAP), dry weight, root volume, root nodules, pod weight, and pod number. Meanwhile, rice husk biochar affected root volume and root nodules. An interaction between guano fertilizer and rice husk biochar was observed in the root nodule variable. The application of guano fertilizer and rice husk biochar at a dose of 10 tons/ha was found to be effective and efficient in enhancing the growth and yield of edamame soybeans.